1992
DOI: 10.1007/bf01182876
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the medial reticular formation of the medulla oblongata in the supraspinal control of locomotor and postural activities in the guinea pig

Abstract: The influence of microinjections of novocaine (1.5 microliters of a 2% solution) into the ventromedial areas of the reticular formation of the medulla oblongata on the effects of electrical stimulation of the mesencephalic locomotor region, and of adequate stimulation of the vestibular apparatus, was investigated in experiments on decerebrate guinea pigs. It was demonstrated that such injections are accompanied by a reversible increase in the threshold of stimulation of the region indicated, necessary for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For example, continuous stimulation of RS neurons is sufficient for initiation of locomotion in a wide variety of vertebrates: lamprey (Jackson et al, 2007); stingray (Livingston and Leonard, 1990); dogfish (Grillner and Wallén, 1984); fish (Uematsu and Todo, 1997); birds (Steeves et al, 1987); and mammals (Ross and Sinnamon, 1984; Garcia-Rill and Skinner, 1987). In addition, in some vertebrates, RS neurons also have been shown to be necessary for initiation of locomotion (Shefchyk et al, 1984; Bernau et al, 1991; Marlinski and Voitenko, 1992; Paggett et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…For example, continuous stimulation of RS neurons is sufficient for initiation of locomotion in a wide variety of vertebrates: lamprey (Jackson et al, 2007); stingray (Livingston and Leonard, 1990); dogfish (Grillner and Wallén, 1984); fish (Uematsu and Todo, 1997); birds (Steeves et al, 1987); and mammals (Ross and Sinnamon, 1984; Garcia-Rill and Skinner, 1987). In addition, in some vertebrates, RS neurons also have been shown to be necessary for initiation of locomotion (Shefchyk et al, 1984; Bernau et al, 1991; Marlinski and Voitenko, 1992; Paggett et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The rubrospinal tract influences movement through direct and reciprocal spinal motor projections that reflect activity of the rubro-cortico-cerebellar premotor pathway Miller and Houk, 1995). The vestibulospinal and reticulospinal tracts affect postural control and balance during locomotion, providing afferent input to premotoneuronal interneurons and ultimately influencing converging and diverse descending motor inputs and the spinal locomotor pattern generator (Dubuc, 1992;Fetcho, 1992;Marlinsky and Voitenko, 1992;Marlinsky, 1992;Perreault et al, 1993;Vinay and Grillner, 1993;Akbarian et al, 1994;Bussieres and Iwakiri et al, 1995;Grillner et al, 1995;Gossard et al, 1996;Pflieger and Cabana, 1996). Specialization in the vestibular system in particular has been important for the evolution of bipedal locomotion in humans (Spoor et al, 1994).…”
Section: Abstract: Corticospinal; Neurotrophin-3 (Nt-3); Spinal Cordmentioning
confidence: 99%
“…Inactivation of NGC/NMC by cooling, chemical injection, and lesion either blocked stepping induced by mesencephalic locomotion region stimulation, or increased the threshold for mesencephalic locomotion region stimulation to induce locomotion [290,347,423]. Our study showed that microinjection of glutamate antagonists into the NMC reversed muscle tone suppression induced by pontine carbachol injection [244].…”
Section: Motor Activitymentioning
confidence: 63%